Social Changes And Conflicts In Orang Sekaum In The North Halmahera Peace Zone - Nur, Abubakar Muhammad (Advances in Social Sciences Research Journal, 2018)
The civilization of "orang sekaum" (ethnic Tobelo) in its development, follows the dynamics of social change that leads to social conflict. Conflict and violence between brothers in "orang sekaum" gave birth to two different poles in a vulgar way (Islam vs. Christian). The process of social change and the development of "orang sekaum" is characterized by a climate of social life that previously lived in a harmonious and peaceful state, turned into conflict between brothers in the peace zone. Communities are provoked and powerless over the presence of migration in North Halmahera, from various regions as victims of previous conflicts and violence. The impact of this violent incident is directly proportional to the instability of the social control castle embodied in the cultural values of "Hibua Lamo" as the social glue and kinship of “orang sekaum” Therefore, horizontal riots soon take place with the same reason and language, each maintaining self-esteem on the basis of beliefs and religions it embraces